Морской охотник: [роман] / Сергей Зверев ; [художник М. Левыкин] - Зверев Сергей Иванович (Морской спецназ, 2006)
Экземпляры: (20200717) / Инвентарный номер: 31264 / Цена: 33.00 / Сис.шифр: Р2 / Авт.знак: З-43 / ГРНТИ: 17 / ББК: 84(2=411.2)6-44